Hypergraph theory : an introduction - Bretto, Alain (Mathematical Engineering, 2013)
This book presents hypergraph theory and covers traditional elements of the theory as well as original concepts such as entropy of hypergraph, similarities and kernels. It details applications in telecommunications and parallel data structure modeling.